Occurrence, antibiogram, high-level vancomycin and aminoglycosides resistance and potential virulence factors of enterococci in dogs in Nigeria - Anyanwu, MU; Eze, UU; Nnamani, JC; Ikenna-Ezeh, NH; Akpa, PO; Okorie-kanu, OJ; Anene, BM (Journal of the Hellenic Veterinary Medical Society, 2023)
Abstract This study was conducted to isolate enterococci from dogs in Nigeria, and to determine the potential virulence, antibiotic susceptibility, phenotypic vancomycin (VAN), high-level ampicillin (AMP) and aminoglycosides susceptibility profile of the isolates. Rectal swabs were collected from 295 randomly-selected, clinically-healthy dogs. The isolation of enterococci was done using Slanetz and Bartley enterococcal selective medium. The resistance of 150 non-repetitive isolates was determined using disc diffusion method. VAN resistance was assessed by high-level disc diffusion and agar-screening methods. High-level AMP and aminoglycosides (gentamicin and streptomycin) resistance was determined by agar-screening method. Potential virulence factors were assayed using phenotypic methods. Out of 295 samples, 234 (80.7%) gave positive growth. From these, 250 enterococcal isolates comprised 229 (91.6%) non-pigmented and 21 (8.4%) pigmented strains, were obtained. Resistance of the isolates was 89% to erythromycin, 92% to rifampicin, 77% to chloramphenicol, 83% to tetracycline, 64% to ciprofloxacin, 32.7% to VAN, 24.7% to high-level streptomycin (HLS) and 6% to high-level gentamicin (HLG). Among 150 non-repetitive resistant isolates, 144 (96%), including all the VAN-, HLS- and HLG-resistant strains, exhibited resistance to at least 3 classes of antibiotics. The mean multiple antibiotic resistance index was 0.54 (range = 0.22 – 0.89). Of these 150 isolates, 94 (62.7%), including all the VAN-, HLS- and HLG-resistant strains, displayed virulence potentials as biofilm (44.7%), surface-layer (13.8%), haemolysin (21.3%), gelatinase (40.4%), caesinase (10.6%) and deoxyribonuclease (12.8%) activities. This study showed that dogs in Nigeria are potential reservoirs and disseminators of potentially-virulent, multidrug-, VAN- and high-level aminoglycosides-resistant enterococci.